2009
DOI: 10.1080/08916930902830979
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-related changes in plasma membrane glycoconjugates of peripheral blood lymphocytes in rheumatoid arthritis

Abstract: Control of apoptosis (apo) is very important for diagnosis, prognosis and treatment of rheumatoid arthritis (RA). Recently, we found that an appearance of specific cell surface GC is attributable to apo and developed lectin-induced agglutination test for apo evaluation. The aim of current study was to estimate changes in surface GC expression in peripheral blood lymphocytes (PBL) of normal healthy donors (NHD) and patients with RA, measured by cell agglutination with the galactose-specific VAA lectin and by le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…Our finding explains the previously known fact of surface glycopattern contribution to the clearance of dying and aged cells (Savill, Fadok, Henson, & Haslett, 1993). We effectively used changed apoptotic cell glycopattern for detection of dying cells in blood samples at the autoimmune disorders (R. Bilyy et al, 2009). We have proved that artificial desialylation of apoptotic and viable cells enhances their clearance by macrophages.…”
Section: Ways To Improve Clearancesupporting
confidence: 60%
See 1 more Smart Citation
“…Our finding explains the previously known fact of surface glycopattern contribution to the clearance of dying and aged cells (Savill, Fadok, Henson, & Haslett, 1993). We effectively used changed apoptotic cell glycopattern for detection of dying cells in blood samples at the autoimmune disorders (R. Bilyy et al, 2009). We have proved that artificial desialylation of apoptotic and viable cells enhances their clearance by macrophages.…”
Section: Ways To Improve Clearancesupporting
confidence: 60%
“…Previously, we (R. Bilyy et al, 2009) demonstrated a significant increase in apoptosis incidence in the perypheral blood lymphocytes of RA patients comparing with lymphocytes of clinically healthy donors. That increase was detected by both flow cytometry and lectin-induced agglutination testing of apoptosis.…”
Section: Lymphocyte Desialylation At Slementioning
confidence: 99%
“…Our results suggest that "the residues of Gal β1,3-GalNAcα1, α-D-mannose, Nacetylgalactosamine or L-fucose in the N-glycoprotein core are involved in apoptosis regardless of the cell type, whereas the L-fucose terminal (Lewis X antigen; LTA)" [55,59] is only involved in the apoptosis of spermatocytes (Figure 1), b) the residues identified by our battery of lectins in apoptotic cells were similar to those found in isolated cell types in apoptosis by other authors: β-D-galactose and α-D-mannose [44,46], L-Fucose (antigen Lewis X) [60] or Nacetylgalactosamine [61] in which the changes we observed in some sugars have been observed in the early stages of apoptosis [44,46,49,62]. These carbohydrates could participate in the identification and removal of apoptotic cells by phagocytes (Sertoli cells), based on their recognition by the 'eat me signals' found on the cell membrane [51]. "These phagocytic cells recognized the signals and rapidly phagocytized the apoptotic cells before they were degraded, thus preventing the inflammatory reaction and protecting tissues from the damaging effects of the potentially harmful intracellular contents [55,61], c) the plasma membrane of apoptotic cells was lectin-positive during their early stages, while their cytoplasm was also lectin-positive in later stages.…”
Section: Apoptosis Identification In Seminiferous Epithelium Through mentioning
confidence: 98%
“…The data revealed an increased level of apoptosis in lymphocytes of RA patients, with high cell surface Glyc expression and with an increased number of cells exposing galactose-rich Glyc. The authors concluded that cell surface Glyc can be used for the detection of apoptotic cells in RA and other autoimmune disorders [51].…”
Section: Identification Of Apoptotic Cells By Lectinsmentioning
confidence: 99%
“…Відповідно пев-ні зміни у цих комплексах можуть провокувати неа-декватну реакцію імунної системи матері на плід. Аналіз динаміки експонування та перерозподілу рецепторів лектинів на поверхні та у складі клітинних компартментів дає змогу оцінювати ступінь диферен-ціювання клітин і тканин загалом, рівень функціо-нальної активності клітин, її здатність до міґрації, фаґоцитозу, ідентифікувати початок незворотних дистрофічних змін і апоптозу [2,5,10,15]. Із огляду на викладене вище, стає очевидною доцільність вив-чення особливостей ґлікопротеїнових та ґліколіпідних комплексів ворсинок хоріона (ВХ) мимовільно елімі-нованих плодів людини в контексті визначення мож-ливих причин їх втрат.…”
unclassified